2022
DOI: 10.1007/s10689-022-00288-y
|View full text |Cite
|
Sign up to set email alerts
|

Colectomy and desmoid tumours in familial adenomatous polyposis: a systematic review and meta-analysis

Abstract: Desmoid tumours (DT) are one of the main causes of death in patients with familial adenomatous polyposis (FAP). Surgical trauma is a risk factor for DT, yet a colectomy is inevitable in FAP to prevent colorectal cancer. This systematic review and meta-analysis aimed to synthesize the available evidence on DT risk related to type, approach and timing of colectomy. A search was performed in MEDLINE, EMBASE and the Cochrane Library. Studies were considered eligible when DT incidence was reported after different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
(54 reference statements)
1
10
0
Order By: Relevance
“…18 Studies looking at whether operative approach (open vs. laparoscopic surgery) contributes to desmoid formation are also inconclusive. A recent meta-analysis showed no significant difference in open versus laparoscopic surgery, 19 while a retrospective review from the St. Mark's Polyposis Registry showed a slightly lower association of desmoid development with laparoscopic TAC/IRA compared with open TAC/IRA. 20 It is the authors' strategy, therefore, in our patients at high risk for desmoid formation to delay surgery as long as is possible and preferentially perform laparoscopic TAC/IRA if the rectum polyp burden can be safely managed endoscopically.…”
Section: Desmoid Risk Factors and Prevention Strategiesmentioning
confidence: 96%
See 1 more Smart Citation
“…18 Studies looking at whether operative approach (open vs. laparoscopic surgery) contributes to desmoid formation are also inconclusive. A recent meta-analysis showed no significant difference in open versus laparoscopic surgery, 19 while a retrospective review from the St. Mark's Polyposis Registry showed a slightly lower association of desmoid development with laparoscopic TAC/IRA compared with open TAC/IRA. 20 It is the authors' strategy, therefore, in our patients at high risk for desmoid formation to delay surgery as long as is possible and preferentially perform laparoscopic TAC/IRA if the rectum polyp burden can be safely managed endoscopically.…”
Section: Desmoid Risk Factors and Prevention Strategiesmentioning
confidence: 96%
“…18 Studies looking at whether operative approach (open vs. laparoscopic surgery) contributes to desmoid formation are also inconclusive. A recent meta-analysis showed no significant difference in open versus laparoscopic surgery,19 while a retrospective review from the St. Mark's Polyposis Registry showed a slightly lower association of desmoid development with laparoscopic TAC/IRA compared with open TAC/IRA.…”
mentioning
confidence: 96%
“…Furthermore, Konishi et al [24] reported that the incidence of DTs was comparable between laparoscopic and open approaches in both total proctocolectomy with IPAA and total colectomy with ileorectal anastomosis (IRA). A very recent report of a systematic review and meta-analysis by Aelvoet et al [48] demonstrated that no significant difference in DT incidence was observed after IRA versus IPAA (OR 0.99, 95% CI 0.69-1.42) and after open versus laparoscopic colectomy (OR 0.88, 95% CI 0.42-1.86). Another systematic review by Xie et al [49] reported that there was no significant difference in the incidence of DTs between IRA and IPAA.…”
Section: Risk Factorsmentioning
confidence: 98%
“…[136][137][138][139] However, conflicting reports suggest that the operative approach and extent of operation result in a similar risk for desmoid formation. [140][141][142][143] Based on the body of retrospective literature with its inherent selection bias, the risk of desmoid tumors after surgical trauma remains unclear and, likely, multifactorial. Other factors, such as APC genotype, family history, and sex, rather than surgical trauma alone, may influence desmoid formation in patients with FAP.…”
Section: Strength Of Recommendation: Strong Based On Moderate-quality...mentioning
confidence: 99%